CEO diversity, political influences, and CEO turnover in unstable environments: The Romanian case - Ingrid-Mihaela Dragotă; Andreea Curmei-Semenescu; Raluca Moscu (Journal of Risk and Financial Management, 2020)
This work expands the literature on a less studied topic, the Chief Executive Officer (CEO) turnover in post-communist economies, analyzed during an unstable and ambiguous economic and financial environment. For the period 2005-2010, the results indicate the political inference in CEO turnover decision for the Romanian listed companies. In this period, with great turmoil in the economy determined by the financial crisis of 2008, we also find that CEO gender helps to explain the probability of changing the CEO. Moreover, this paper empirically tests if the financial and corporate governance determinants that are validated in the existing literature work for the Romanian listed companies. We reinforce that CEO turnover decision is negatively related to accounting-based performance. We find evidence of the "voting with their feet" behavior of institutional investors, and of the lack of Board of Directors monitoring. The CEO-Chairman duality and the controlling power of the largest shareholder act as entrenchment mechanisms.
Keywords: 330; CEO turnover; foreign CEO; female CEO; ownership structure; Romania